2009
DOI: 10.1103/physrevlett.102.244101
|View full text |Cite
|
Sign up to set email alerts
|

Pinned Scroll Rings in an Excitable System

Abstract: Three-dimensional spiral waves in the Belousov-Zhabotinsky reaction are pinned to unexcitable heterogeneities. This pinning can prevent the collapse of scroll rings even if the heterogeneity does not extend along the entire wave filament. In the latter case, frequency differences create stationary gradients in the rotation phase. These twist patterns and their frequencies agree with algebraic solutions of the forced Burgers equation revealing insights into the phase coupling of scroll waves.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
39
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 23 publications
2
39
0
Order By: Relevance
“…Our results reveal the formation of vortex structures in which neighboring filament branches are stationary despite strong curvature. The experimental preparation of these states relies on recent advances that allow the pinning of scroll waves to inert and impermeable heterogeneities [22][23][24]. A comparison with curvature-flow simulations yields quantitative information on the distance-dependence of filament interaction.…”
mentioning
confidence: 99%
“…Our results reveal the formation of vortex structures in which neighboring filament branches are stationary despite strong curvature. The experimental preparation of these states relies on recent advances that allow the pinning of scroll waves to inert and impermeable heterogeneities [22][23][24]. A comparison with curvature-flow simulations yields quantitative information on the distance-dependence of filament interaction.…”
mentioning
confidence: 99%
“…Using (14), the parameter plane of D 1 as a function of k for b = 1 were plotted in Fig. 1, which is divided into two regions.…”
Section: Dependence Of Output Signal Amplitude On Multiplicative Noismentioning
confidence: 99%
“…Examples include investigations of scroll waves pinned to inert obstacles such as tori, double tori, spheres, and cylinders [25,[28][29][30]. These experiments have revealed that pinning qualitatively alters the evolution of the filament and often results in lifetime enhancement or complete stabilization of vortices that, in the absence of pinning sites, would rapidly shrink and annihilate.…”
Section: Introductionmentioning
confidence: 99%